Biliary tract malignancies: a population-based study on incidence, prognosis and management of patients. (1st December 2016) - Juliusson, Gunnar; Jonasson, Jon Gunnlaugur; Jonsdottir, Sara B.; Garcia, Henrik G.; Olafsdottir, Elinborg; Möller, Pall Helgi; Björnsson, Einar S.
Abstract: Background: Biliary tract malignancies are uncommon and few population-based studies are available. Methods: This nationwide population-based study in Iceland included all patients diagnosed with intra- and extrahepatic cholangiocarcinoma, gallbladder and ampullary cancer from 1984 to 2012. Patients were identified through the Icelandic Cancer Registry. Clinical information was obtained from patient records. Results: Overall 245 patients were identified: 38 had intrahepatic cholangiocarcinoma, 66 extrahepatic cholangiocarcinoma, 73 gallbladder cancer (GBC) and 68 ampullary cancer. Overall incidence for bile tract malignancies was 1–3 per 100, 000 person-years and less than 1 by sub-type. The overall bile tract malignancies in males increased from 1.3 (95% CI 0.8–1.8) to 2.5 (1.9–3.1) per 100, 000 inhabitants. The incidence of GBC among females decreased from 1.1 (0.7–1.5) to 0.5 (0.2–0.7). Surgery decreased for extrahepatic cholangiocarcinoma (56 to 23%, p  = .027), ampullary cancer (80 to 48%, p  = .03) and overall bile tract cancer (61 to 32%, p  < .0001) but use of chemotherapy increased (4 to 32%, p  < .0001). Five-year relative survival rates for men were 15% and 24% for women. No significant improvement was found in survival. Conclusions: Overall incidence of bile tract malignancies increased in males and GBC decreased in women. Long-term survival is poor and did not improve despite changes in treatment.